A Consistency-checking Consensus-building Method to Assess Complexity of Energy Megaprojects. (14th July 2016) - Kian, M.R. Ehsan; Sun, Ming; Bosché, Frédéric
Abstract: Project complexity has been recognised as one of the main causes of failures in many energy megaprojects worldwide. This research aims to develop a Project Complexity Assessment (PCA) method, which consists of three components: a taxonomy of Project Complexity Indicators (PCIs), an integrated Delphi and Analytic Hierarchy Process (AHP) process to establish weights of the PCIs, and numerical rating criteria for all PCIs. An innovative aspect of the research is the effective consistency checking and consensus building method during the Delphi-AHP process. The developed PCA method is demonstrated in an energy megaproject case study.